Influence of training on the response of androgen plasma concentrations to exercise in swimmers - Bonifazi, M.; Bela, E.; Carli, G.; Lodi, L.; Martelli, G.; Zhu, B.; Lupo, C. (European Journal of Applied Physiology, 1995)
In eight top-level male endurance swimmers the aerobic performance and the response to exercise of total testosterone (T), free testosterone (fT), sex hormone binding globulin (SHBG), non-SHBG-bound testosterone (NST) and cortisol (C) were evaluated during a training season. The swimmers participated in three test sessions which occurred 6, 12 and 24 weeks after the beginning of the season. During each session, after a standard warm-up, the swimmers performed a set of 15 x 200-m freestyle, with a 20-s rest between repititions, at a predetermined individual speed. Three blood samples were collected: before warm-up, at the end of the set, and after 1 h of recovery. A few days before each session, the individual swimming velocity associated with a 4 mmol.l-1 blood lactate concentration (v4) was assessed as a standard of aerobic performance. The values of v4 were lower in the second session than in the third one. The concentrations of C. which increased after the exercise, showed the highest values in the second session. The values of T and the T:SHBG ratio increased after the exercise but returned to their initial concentrations during the recovery period. The values of fT and NST increased after the exercise in the first and third sessions. In the initial two sessions, when the aerobic performance was still low, the concentrations of NST decreased to below the initial values after recovery. In session III, when the adaptation to the training workload was complete, NST returned to resting concentrations after recovery.